Fabrication and Characterization of Collagen/PVA Dual-Layer Membranes for Periodontal Bone Regeneration - Zhou, Tian; Chen, Siwei; Ding, Xinxin; Hu, Zhihuan; Cen, Lian; Zhang, Xiaomeng (Frontiers in Bioengineering and Biotechnology, 2021)
Guided tissue regeneration (GTR) is a promising treatment for periodontal tissue defects, which generally uses a membrane to build a mechanical barrier from the gingival epithelium and hold space for the periodontal regeneration especially the tooth-supporting bone. However, existing membranes possess insufficient mechanical properties and limited bioactivity for periodontal bone regenerate. Herein, fish collagen and polyvinyl alcohol (Col/PVA) dual-layer membrane were developed via a combined freezing/thawing and layer coating method. This dual-layer membrane had a clear but contact boundary line between collagen and PVA layers, which were both hydrophilic. The dual membrane had an elongation at break of 193±27% and would undergo an in vitro degradation duration of more than 17 days. Further cell experiments showed that compared with the PVA layer, the collagen layer not only presented good cytocompatibility with BMSCs, but also promoted the osteogenic genes (RUNX2, ALP, OCN, COL1) and protein (ALP) expression of rat bone marrow-derived mesenchymal stem cells. Hence, the currently developed dual-layer membranes could be used as a stable barrier with a stable degradation rate and selectively favour the bone tissue to repopulate the periodontal defect. The membranes could meet the challenges encountered by GTR for superior defect repair, demonstrating great potential in clinical applications.